Procedures using diffuse reflectance spectroscopy for estimating hematite and goethite in Oxisols of São Paulo, Brazil - De Souza Bahia, Angélica Santos Rabelo [UNESP]; Marques, José [UNESP]; Siqueira, Diego Silva [UNESP] (Elsevier, 2015)
Abstract This work aims to evaluate the accuracy of different procedures using diffuse reflectance spectroscopy for estimation for iron oxides in the soil. Soil samples were collected at a depth of 0.00-0.20 m in two study areas, with iron oxide content ranging from 22 to 253 g kg- 1. Hematite (Hm) and goethite (Gt) were quantified using two techniques: X-ray diffraction (XRD) and diffuse reflectance spectroscopy (DRS). The Hm and Gt contents determined by XRD were explained by the content of Hm and Gt estimated by DRS with 99 and 79% accuracy, respectively. The analysis of the amplitude of spectral bands in the second derivative and the continuum removal technique showed higher values of the parameters of the regression equation compared to XRD technique. Considering the time and costs to perform iron oxide analyses, the procedures using DRS were the ones that provided regressions that are able to adjust with greater accuracy the mineral contents, providing explanatory pedotransfer models, compared to oxides obtained by the XRD technique. These results are extremely important because they show great potential of this tool and can help the detailed mapping of various soil attributes based in the mineralogy.
Keywords: Brazilian Oxisols; Continuum removal technique; Pedometrics; Pedotransfer functions; X-ray diffraction